SULTR3;1 is a chloroplast-localized sulfate transporter in Arabidopsis thaliana - Cao, Minjie; Wirtz, Markus; Hell, Rüdiger (The plant journal, 2012)
Plants play a prominent role as sulfur reducers in the global sulfur cycle. Sulfate, the major form of inorganic sulfur utilized by plants, is absorbed and transported by specific sulfate transporters into plastids, especially chloroplasts, where it is reduced and assimilated into cysteine before entering other metabolic processes. How sulfate is transported into the chloroplast, however, remains unresolved; no plastid-localized sulfate transporters have been previously identified in higher plants. Here we report that SULTR3;1 is localized in the chloroplast, which was demonstrated by SULTR3;1-GFP localization, Western blot analysis, protein import as well as comparative analysis of sulfate uptake by chloroplasts between knockout mutants, complemented transgenic plants, and the wild type. Loss of SULTR3;1 significantly decreases the sulfate uptake of the chloroplast. Complementation of the sultr3;1 mutant phenotypes by expression of a 35S-SULTR3;1 construct further confirms that SULTR3;1 is one of the transporters responsible for sulfate transport into chloroplasts.
Gesehen am 11.05.2017